Viability of Lactobacillus from Breast Milk Isolate in Upper Digestive Tract by In Vitro - Hapsari Arihantana, Ni Made Indri; Puspawati, Ni Nyoman (Journal of Food Security and Agriculture; Vol 1 No 2 (2017): Journal of Food Security and Agriculture, 2017)
Transformation in lifestyle and eating habits can change the stability of flora ecosystems in the gut. This condition can be altered by increasing the number of good bacteria to reduce the number of pathogenic bacteria. This can be achieved by consuming functional foods containing probiotic bacteria. Probiotics are living bacteria found in food products and supplements. These bacteria have many benefits for the health of the body, especially for the digestive tract and can help balance the intestinal microbiota. Probiotics from lactic acid bacteria (LAB) classification, especially Lactobacillus genus is part of the normal flora of the human digestive tract. One of the conditions for bacteria to be a probiotic culture is to be able to survive in high stomach acid in the digestive tract. This study used 5 species of LAB breast milk isolates: L. plantarum 1 A1, L. plantarum 1 A8, L. plantarum 1 B8, L. rhamnosus A6, and L. rhamnosus B10b which were tested it’s ability to survive high acid conditions in the upper digestive tract by in vitro. This is done to determine whether the five isolates have the ability as probiotic bacterias. From the results of the study it was found that at pH 2 there was a decrease between 2 - 5 log cycles where the highest resistance of LAB breast milk isolate was L. rhamnosus A6. At pH 3 there was a decrease between 1 - 7 log cycles, where L. plantarum 1 A1, L. plantarum 1 A8, and L. rhamnosus B10b has the highest resistance. At pH 4 there was a decrease between 1 -3 log cycles with the five isolates of LAB that were able to survive at pH 4.